2018
DOI: 10.1002/ijc.31656
|View full text |Cite
|
Sign up to set email alerts
|

Functional variant of MTOR rs2536 and survival of Chinese gastric cancer patients

Abstract: We previously reported that some single nucleotide polymorphisms (SNPs) of candidate genes involved in the MTOR complex1 (MTORC1) were associated with risk of gastric cancer (GCa). In the present study, we further evaluated associations of eight potentially functional SNPs of MTOR, MLST8 and RPTOR with survival of 1002 GCa patients and also investigated molecular mechanisms underlying such associations. Specifically, we found that the MTOR rs2536 C allele at the microRNA binding site was independently associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In particular, WWOX was demonstrated to be closely interacted with mTOR 13 and DNA repair 14 pathways whose genetic variants were our previous focus. Genetic variants in mTOR 9 and DNA repair pathways 6 were found to have significant survival associations with GCa patients in our previous work. However, so far, no study has explored the association between genetic variants in WWOX and the survival of GCa patients.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In particular, WWOX was demonstrated to be closely interacted with mTOR 13 and DNA repair 14 pathways whose genetic variants were our previous focus. Genetic variants in mTOR 9 and DNA repair pathways 6 were found to have significant survival associations with GCa patients in our previous work. However, so far, no study has explored the association between genetic variants in WWOX and the survival of GCa patients.…”
Section: Introductionmentioning
confidence: 75%
“…Precise prediction of prognosis is extremely necessary in guiding treatment decisions for GCa patients at different death risks 21,22 . We previously found that some SNPs involved in DNA repair 6 and mTOR pathway 9 were survival predictors in GCa patients. Importantly, the present study found genetic variants in WWOX , a gene closely related to DNA repair 14 and mTOR 13 pathway genes, to also be associated with the survival of GCa patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation